Sifat-sifat Fisik Sosis Berbahan Baku Surimi-like Daging Kambing dengan Menggunakan Susu Kedelai Sebagai Binder - Mega, Olfa; S, Suharyanto; Badarina, Irma (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2014)
Â The purpose of this study was to evaluated physical properties of sausage made from meat goat surimi-like as affected by using soya milk as binder. The study was designed as block randomized design at four treatments and three replications included on the block, those were 0% ,2%, 4% and 6% soya milk as substitusion skim milk. The amount of binder was 6% of meat. weight. Data were analyzed using analysis of variance and Duncan Multiple of Range Test. The results showed that using soya milk as binder significantly (P<0,01) decreased pH, firmness and cooking loss, while water holding capacity of sausage increased. Using soya milk 6% as binder improve water holding capacity, cooking loss and fimness.